Current and future molecular diagnostics in non-small-cell lung cancer. (August 2015) - Li, Chun Man; Chu, Wing Ying; Wong, Di Lun; Tsang, Hin Fung; Tsui, Nancy Bo Yin; Chan, Charles Ming Lok; Xue, Vivian Wei Wen; Siu, Parco Ming Fai; Yung, Benjamin Yat Ming; Chan, Lawrence Wing Chi; Wong, Sze Chuen Cesar
<x xml:space="preserve">Abstract</x> The molecular investigation of lung cancer has opened up an advanced area for the diagnosis and therapeutic management of lung cancer patients. Gene alterations in cancer initiation and progression provide not only information on molecular changes in lung cancer but also opportunities in advanced therapeutic regime by personalized targeted therapy. EGFR mutations and ALK rearrangement are important predictive biomarkers for the efficiency of tyrosine kinase inhibitor treatment in lung cancer patients. Moreover, epigenetic aberration and microRNA dysregulation are recent advances in the early detection and monitoring of lung cancer. Although a wide range of molecular tests are available, standardization and validation of assay protocols are essential for the quality of the test outcome. In this review, current and new advancements of molecular biomarkers for non-small-cell lung cancer will be discussed. Recommendations on future development of molecular diagnostic services will also be explored.